2022
DOI: 10.1530/rep-22-0036
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated changes in miRNA profile of bovine follicular fluid

Abstract: We examined age-associated changes in microRNA (miRNA) profiles in the follicular fluid (FF) of cows. The role of miR-19b, which is abundant in the FF of young cows, in in vitro growth of early antral follicles (EAFs)-derived oocytes was assessed. FF was collected from the antral follicles of young (20–40 months) and aged (>120 months) cows. The miRNA profiles were similar between the FF of both age groups, whereas the abundance of some miRNAs differed between these samples. The miRNA profiles in granulosa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The miRNA profiles of the FFs found in the present study also overlapped with those reported in cows. 21 , 24 Furthermore, many miRNAs found in human FFs overlap with the miRNAs found in this study. 32 Based on these reports, the top miRNAs in the EVs of FF are conserved among cows and resemble those in humans.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…The miRNA profiles of the FFs found in the present study also overlapped with those reported in cows. 21 , 24 Furthermore, many miRNAs found in human FFs overlap with the miRNAs found in this study. 32 Based on these reports, the top miRNAs in the EVs of FF are conserved among cows and resemble those in humans.…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, we previously showed that miRNA profiles in GCs differ from the profiles in the spent culture medium of GCs. 21 These results suggest that certain groups of miRNAs are selectively packaged into the EV for secretion.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Herein, the gel culture system activated genes associated with the focal adhesion and actine-mediated signal transduction; however, the key factors causing these changes are yet to be defined. RNA-sequencing (RNA-seq) technology combined with ingenuity upstream regulator analysis (IPA) is useful for identifying the molecules that cause the differential expression of genes in granulosa cells, embryos, and uterine epithelial cells [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%